2005
DOI: 10.1179/174327805x79511
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and protection of lead anodes in acidic copper sulphate solutions

Abstract: It is known that lead anodes used in the industrial extraction of copper by electrolysis (electrowinning) suffer corrosion as a result of accidental or intended current interruptions. In order to improve understanding of the corrosion and protection of such anodes, the effects of the concentrations of copper, sulphuric acid, cobalt, iron, manganese, chloride and an organic additive (guar) on the corrosion of lead have been studied by means of weight loss tests and surface analysis techniques (X-ray photoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…This process is performed using the electrochemical reactions of water oxidation on a lead anode 2,3,4 and zinc reduction in a solution on an aluminum cathode.Within the zinc electro-winning process, in spite of having being used for several years, there are two major drawbacks: the first is the generation of acid mist produced by the O 2 evolution reaction at the anode, which causes damage to the working plant. The second of these is the use of lead anodes.…”
Section: Methodsmentioning
confidence: 99%
“…This process is performed using the electrochemical reactions of water oxidation on a lead anode 2,3,4 and zinc reduction in a solution on an aluminum cathode.Within the zinc electro-winning process, in spite of having being used for several years, there are two major drawbacks: the first is the generation of acid mist produced by the O 2 evolution reaction at the anode, which causes damage to the working plant. The second of these is the use of lead anodes.…”
Section: Methodsmentioning
confidence: 99%
“…The corrosion products, from the samples, are removed by their dissolution in water solution of 100 g l À1 KOH þ 50 g l À1 KI þ 200 g l À1 Na-tartarate at 30 8C [11]. Samples, previously washed in deionized water and then in absolute methanol and dried in warm air, are weighted on the analytical balance.…”
Section: Weight Loss Measurement Of Corrosion Ratementioning
confidence: 99%
“…It is seen from Figs. 4 and 5 that concentration of tin in the alloy should be !1.1 wt% to obtain its positive effect on the microstructure refinement, as well as the addition of 0.02 wt% of silver [1,5,6,10,11].…”
Section: Thermo-mechanical Treatment Of Cast Alloys Into Sheet Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…Problems related to manganese in the electrolyte have been discussed by Miller (1995) and Hughes et al (1998). Cifuentes et al (2005) investigated the effect of various impurities in a copper electrowinning electrolyte on the rate of corrosion of lead anodes and found that manganese increased the corrosion rate of lead anodes more significantly during normal tankhouse operation than during current interruptions. The PbSO 4 formed in Equation [11] is also converted to PbO 2 at the anode but it will be in the form of loose, nonadherent flakes.…”
mentioning
confidence: 99%